2016
DOI: 10.1093/jxb/erw425
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of extracellular invertase inhibitor gene expression improves seed weight in soybean (Glycine max)

Abstract: HighlightThe roles of GmCIF1 and GmC/VIF1 as invertase inhibitors were examined in vitro in soybean (Glycine max), and post-translational elevation of extracellular invertase activity by silencing GmCIF1 expression was found to increase seed weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 68 publications
3
67
0
Order By: Relevance
“…By contrast, silencing of CIF expression also facilitated the improvements of seed filling, prolonged leaf green, and cold tolerance in tomato (Jin et al, 2009;Xu et al, 2017), highlighting that the post-translational control is necessary for hexoses to release to sink organs, particularly responding to stressors and phytohormone cues. These results corroborated the findings that the suppression of CIF expression resulted in increased seed production and germination (Su et al, 2016;Tang et al, 2017). An increasing body of evidence supported the notion that the C/ VIF-mediated post-translational modulation of invertase commonly involves multiple cellular processes, metabolic pathways, and molecular regulation.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…By contrast, silencing of CIF expression also facilitated the improvements of seed filling, prolonged leaf green, and cold tolerance in tomato (Jin et al, 2009;Xu et al, 2017), highlighting that the post-translational control is necessary for hexoses to release to sink organs, particularly responding to stressors and phytohormone cues. These results corroborated the findings that the suppression of CIF expression resulted in increased seed production and germination (Su et al, 2016;Tang et al, 2017). An increasing body of evidence supported the notion that the C/ VIF-mediated post-translational modulation of invertase commonly involves multiple cellular processes, metabolic pathways, and molecular regulation.…”
Section: Introductionsupporting
confidence: 81%
“…The previously described C/VIFs (Link et al, 2004;Tang et al, 2017) were collected as queries to search for the homologs in P. trichocarpa genome assembly (3.0) from the JGI gene catalog (Phytozome v12.1, https://phytozome.jgi.doe.gov/pz/portal. html) with the E-value cutoff set as 1e-5 and GenBank (https:// www.ncbi.nlm.nih.gov/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in expression of GmSPS genes in seeds of the three cultivars ( Figure 5E-H) reflected the change in SPS activity ( Figure 4E), which suggests that the four GmSPS homologs acted together to control sucrose synthesis in drought-stressed seeds. Previous studies have reported that loss-of-function invertase mutants had lower invertase activity and thus lower seed weights [51][52][53][54], which indicated that invertase activity had a critical role in the regulation of seed development. The role of SuSy gene was also important for carbon allocation during seed filling, especially when subjected to drought, cold, and heat stress [14,55].…”
Section: Drought Stress Affects Carbohydrate Enrichment and Metabolismentioning
confidence: 96%
“…Heterologous expression of ShINH1 confirmed its possible function as an invertase inhibitor [48]. In the same way, an apoplastic invertase inhibitor was shown to affect seed mass in soybean by regulating extracellular invertase during seed maturation [49]. Invertase inhibitor ZM-INVINH1 has been reported to bind cell wall invertase during grain development in maize [50].…”
Section: Discussionmentioning
confidence: 74%